The Influence of Entrepreneurship Education on Entrepreneurial Motivation among Generation Alpha through Entrepreneur Mindset as a Mediating Variable - Andi Naila Quin Azisah Alisyahbana; Riski Aprilianti Baharuddin; Afnina Afnina; Mas'ud Mas'ud; Jeffrey Chidera Ogeawuchi (Pinisi Journal of Entrepreneurship Review, 2026)
This study aims to examine the effect of entrepreneurship education on entrepreneurial motivation among Generation Alpha in Indonesia by incorporating entrepreneur mindset as a mediating variable. The topic is important due to the growing role of younger generations in the digital economy and the increasing need to develop entrepreneurial competencies from an early age. This study employed a quantitative research approach with 700 Generation Alpha respondents selected using purposive sampling techniques. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 3. The findings indicate that entrepreneurship education has a positive and significant effect on entrepreneurial motivation and entrepreneur mindset among Generation Alpha in Indonesia. Entrepreneurial motivation also positively influences entrepreneur mindset. In addition, entrepreneur mindset significantly mediates the relationship between entrepreneurship education and entrepreneurial motivation. The results suggest that entrepreneurship education contributes not only to increasing entrepreneurial motivation but also to strengthening entrepreneurial thinking patterns among younger generations. This study highlights the importance of support from educational institutions, families, and government in fostering entrepreneurial competencies and motivation among Generation Alpha. The findings provide both theoretical and practical contributions to the development of entrepreneurship education in Indonesia.